2020
DOI: 10.3390/coatings10030300
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Wear Resistance of FeCoCrNi-Mo High Entropy Alloy/Diamond Composite Coatings by High Speed Laser Cladding

Abstract: FeCoCrNi-Mo high entropy alloy/diamond composite coatings were successfully prepared by high speed laser cladding. A high scanning speed was adopted (>30 mm/s), and the effects of laser power, scanning speed, and diamond content on the microstructure and wear resistance of the composite coating were studied. The processing parameters of laser cladding had significant influence on the dilution ratio, graphitization of diamond, and wear resistance of the composite coatings. When the laser cladding parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…And the dilution ratio of V7-V21 are 26.82%, 26.22%, 20.11%, 19.11%, 14.52%, 14.46%, 10.47% and 10.17% respectively, concluded by η= h/ (h + H) [35].…”
Section: Nanoindentationmentioning
confidence: 99%
“…And the dilution ratio of V7-V21 are 26.82%, 26.22%, 20.11%, 19.11%, 14.52%, 14.46%, 10.47% and 10.17% respectively, concluded by η= h/ (h + H) [35].…”
Section: Nanoindentationmentioning
confidence: 99%
“…Different laser power has different effects on the morphology and performance of the coating. Wang et al [26] found that when the laser power is 3000 W, the mechanical properties of the FeCoCrNiMo coating reach the best.…”
Section: Introductionmentioning
confidence: 99%
“…The paper "Microstructures and Wear Resistance of FeCoCrNi-Mo High Entropy Alloy/Diamond Composite Coatings by High Speed Laser Cladding" by Wang et al is devoted FeCoCRNi-Mo high entropy alloy/diamond composite coatings by laser cladding to be used as highly abrasive and wear resistance surface [9]. The authors explain the components proportion and processing parameters optimization to avoid graphitization and diamond thermal damage, and to improve bonding to the metallic matrix.…”
Section: Surface Treatment By Laser-assisted Techniquesmentioning
confidence: 99%
“…Metal-diamond composite coatings are produced by laser cladding by the use of continuous wave diode laser irradiation with optical power in the range 3.0-5.5 kW, robot scanning speed between 30 and 60 mm/s, 4.6 mm spot size, and coaxial powder delivery [9]. Thermal barrier ceramic coatings on a high temperature nickel super alloy are deposited by laser cladding by means of continuous wave diode laser irradiation with optical power in the range 3.5 kW, 10 mm/s scanning speed, 5 mm × 5 mm spot size, and preplaced powder [11].…”
Section: Perspectivesmentioning
confidence: 99%